A Novel Self‐protection Hydroquinone Electrochemical Sensor Based on Thermo‐sensitive Triblock Polymer PS‐PNIPAm‐PS. Issue 6 (28th February 2020) - Zhao, Pengcheng; Ni, Meijun; Chen, Chao; Wang, Chenxi; Yang, Pingping; Wang, Xiahui; Li, Chunyan; Xie, Yixi; Fei, Junjie
Abstract: A novel self‐protection sensor was successfully constructed based on an interesting thermo‐sensitive triblock polymer PS‐PNIPAm‐PS. At low temperatures (<24 °C), the analyte was able to undergo the redox process at the modified electrode. However, the polymer shrunk and accumulated at high temperatures (>30 °C), which dramatically increased the electron transfer resistance (Rct) of the modified electrode and consequently blocked the occurrence of the redox reaction to protect the electrode from high temperatures and enhance its stability. Under optimized conditions, the proposed sensor showed a good detection range for hydroquinone (6×10 −7 to 2.35×10 −3 M) and a low LOD (490 nM). The sensor was also successfully applied for detecting hydroquinone in real samples. The present work may provide a novel method for electrode protection, high‐temperature alarm, high‐temperature protection of batteries and new sensors production. Abstract :